The status of women in the Ancient East: peculiarities of marriage and family relations in Mesopotamia - I. A. Lohvynenko; Ye. S. Lohvynenko (Law and Safety)
The main criteria of social differentiation of women in the first state formations of the Middle Ages have been studied. The influence of religion on the formation of understanding of the place and role of women in society has been shown. Peculiarities of marriage and family relations in ancient Mesopotamia have been considered. The factors determining the social hierarchy of women in the ancient civilizations of the Biennial have been determined and analyzed. The causes of temple and street mass prostitution have been clarified. Features of the position of female slaves have been described.